Evaluating the effect of silver nanoparticles incorporation on antifungal activity and some properties of soft denture lining material - Moamin I Issa; Nabeel Abdul-Fattah (College of Dentistry/ University of Baghdad, 2015)
Background: Colonization of soft denture liners by Candida albicans and other microorganisms continued to be a serious problem. The aim of this study was to evaluate the effect of incorporating silver nanoparticles into heat cured acrylic-based soft denture liner on the antifungal activity, and on water sorption, solubility, shear bond strength and color change of the soft lining material. Furthermore, evaluating the amount of silver released. Materials and methods: Silver nanoparticles were incorporated into soft denture liner in different percentages (0.05%, 0.1% and 0.2% by weight). Four hundred and twenty specimens were prepared and divided into five groups according to the test to be performed. The antifungal activity of the soft liner/AgNPs composite was evaluated in three different periods by using (viable count of C. albicans and disk-diffusion test). The amount of silver released in artificial saliva was measured by atomic absorption spectroscopy. The water sorptions, solubility, shear bond strength and color change was measured and the results were statistically analyzed. Results:All experimental groups showed a highly significant decrease in colony forming units of C. albicans in comparison to control group. There was no inhibition zone around any test specimen of any test group. There was no silver detected to be released. The addition of AgNPs resulted in a highly significant decrease in water sorption, while only 0.2% group showed highly significant decrease in solubility. Non significant differences in shear bond strength were found. A highly significant increase in light absorption percentage was observed in all experimental groups. Conclusion: The addition of AgNPs helps to produce soft denture liner with antifungal properties. Silver was not detected to be released. This addition resulted in decrease in water sorption, and did not affect the shear bond strength and it increased the opacity of the material.